2008
DOI: 10.1111/j.1474-9726.2008.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Aging‐related changes in astrocytes in the rat retina: imbalance between cell proliferation and cell death reduces astrocyte availability

Abstract: SummaryThe aim of this study was to investigate changes in astrocyte density, morphology, proliferation and apoptosis occurring in the central nervous system during physiological aging. Astrocytes in retinal whole-mount preparations from Wistar rats aged 3 (young adult) to 25 months (aged) were investigated qualitatively and quantitatively following immunofluorohistochemistry. Glial fibrillary acidic protein (GFAP), S100 and Pax2 were used to identify astrocytes, and blood vessels were localized using Griffoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 88 publications
3
53
1
1
Order By: Relevance
“…48 A previous study reported that the complicated processes of retinal astrocytes was observed as an aging sign of rat retina. 54 However, the enlargement of the endfeet of retinal astrocytes around blood vessels was much more often observed in the aged TET-1 mice than in the aged Non-tg mice, suggesting an effect of overexpressed ET-1 on astrocytes in our study. One of the possibilities of this phenomenon is end-feet edema, which may suggest the functional deficiency of BRB in the TET-1 mice.…”
Section: Relationship Of Tet-1 Mice With Ntg and Other Vascular-relatcontrasting
confidence: 52%
“…48 A previous study reported that the complicated processes of retinal astrocytes was observed as an aging sign of rat retina. 54 However, the enlargement of the endfeet of retinal astrocytes around blood vessels was much more often observed in the aged TET-1 mice than in the aged Non-tg mice, suggesting an effect of overexpressed ET-1 on astrocytes in our study. One of the possibilities of this phenomenon is end-feet edema, which may suggest the functional deficiency of BRB in the TET-1 mice.…”
Section: Relationship Of Tet-1 Mice With Ntg and Other Vascular-relatcontrasting
confidence: 52%
“…For example, in rat retinal preparations, aging was associated with a decrease in the total number of astrocytes and with an increase in the proportion of cells with gliotic morphology. 159,160 Conversely, a rather significant (by one third) increase in the number of astrocytes was observed in hippocampus of female B57 mice 161 ; similar age-dependent increase in astrocytes quantity was found in the CA1 hippocampal area and in the frontal cortex of male Sprague-Dawley rats; this was accompanied with hypertrophic remodeling that was more prominent in the cortex. 162 An increase (by ϳ20%) in the number of astrocytes was detected in parietal cortex and the dentate gyrus of old Wistar rats.…”
Section: Morphology and Numbersmentioning
confidence: 63%
“…*p<0.05 versus the value of the young rats (fixed as 1); #p<0.05 versus the amount from the same region of aged AL rats; n number of analyzed animals several reasons. Reports on variations of astrocytes density during aging are conflicting, with papers showing either increase, decrease, or no change (see Mansour et al 2008). At most, Cotrina and Nedergaard (2002) reported a 20 % increased density with aging.…”
Section: Discussionmentioning
confidence: 99%